The needs for developing the SABU-SABU method to increase the reading interest of students through digital libraries - Fatkhi, Nadhiyatul; Achyar, Novriyanti (Research in Education and Technology (REGY), 2024)
The literacy level in Indonesia is still low, namely ranking 62nd out of 70 countries with an average literacy score of 397 compared to developed countries of 493. This is proven by the low reading interest of students in schools in Indonesia. The research methodology used qualitative with a sample of 43 students from a population of 110. From the research results, it was found that student’s interest in reading at SMAN 19 Tebo was still low. For this reason, it is necessary to develop a method that can increase student’s interest in reading at the high school level, especially at SMAN 19 Tebo.